Exploring athletes` and classifiers` experiences with and understanding of classification in Para sport - Lawson, J. A.; Williams, T.; Latimer-Cheung, A. E. (Qualitative Research in Sport, Exercise and Health, 2023)
Classification is a defining feature of Para sport; however, little empirical evidence describes the experience of classification and how it can be improved. To date, the primary focus of research related to classification has been on the development of evidence-based classification procedures. Meanwhile, the limited literature which has focused on experiential aspects of classification has shown classification to be a potentially negative experience for athletes. As well, classifiers have been identified as important social actors within the Para sport context, yet no research has examined both athletes` and classifiers` experiences with classification. The experiences of athletes and classifiers have yet to be considered alongside one another. Therefore, the purpose of this study was to elucidate athletes` and classifiers` experiences with classification in Para sport. Semi-structured interviews exploring the experience of classification were conducted with 18 internationally classified Canadian athletes and an international sample of eight classifiers. Hermeneutic phenomenological analysis was used to conceptualise athletes` and classifiers` classification experience. Results demonstrate athletes and classifiers learn about classification by observing others and reflecting on their own understanding of their body or skillset in relation to classification. Additionally, we show how interactions between athletes and classifiers influence each parties` experience quality and highlight discrepancies between each groups` understandings of classification. Next, we provide recommendations for future research to address the identified gaps in athletes` and classifiers` understanding of classification. Lastly, through the provision of practical recommendations, this work may support Para sport practitioners in improving athletes` and classifiers` experiences with classification.